PELATIHAN PERCAKAPAN KALIMAT SINGKAT DALAM BAHASA INGGRIS DENGAN MENGUNAKAN VIDEO PADA SISWA DI SMKS 3 AL WASHLIYAH TAHUN 2025 - Risnawaty; Yulia Arfanti; Saiful Bahri; Ihsan Fadhilah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Based on the description of the partner's problem above, the solution offered by the service team to the problem faced by Suka Cipta Village, Kutalimbaru District is to provide English training by practicing pronouncing words in English as a capital to be able to speak English well so as to increase motivation to learn English. The immersion team used a collaborative strategy, as this immersion focused on English language training so that the immersion team took the initiative to increase the achievement learning motivation of the community in terms of English. This collaborative strategy was used to practice their English speaking skills. The collaborative strategy constitutes a unique and interesting learning strategy. This strategy centers on the activeness of the community in the learning process so that the participants play an active role in the learning. They will have various activities within the strategy. This left the participants unsaturated by the time the learning took place. Thus the participants will be more enthusiastic in learning, which will ultimately make their achievement increase.